Enhanced Diagnostic Capability for Glaucoma of 3-Dimensional Versus 2-Dimensional Neuroretinal Rim Parameters Using Spectral Domain Optical Coherence Tomography. Issue 5 (May 2017) - Fan, Kenneth C.; Tsikata, Edem; Khoueir, Ziad; Simavli, Huseyin; Guo, Rong; A. de Luna, Regina; Pandit, Sumir; Que, Christian J.; de Boer, Johannes F.; Chen, Teresa C.
Abstract : Purpose: To compare the diagnostic capability of 3-dimensional (3D) neuroretinal rim parameters with existing 2-dimensional (2D) neuroretinal and retinal nerve fiber layer (RNFL) thickness rim parameters using spectral domain optical coherence tomography (SD-OCT) volume scans. Materials and Methods: Design: Institutional prospective pilot study. Study population: 65 subjects (35 open-angle glaucoma patients, 30 normal patients). Observation procedures: One eye of each subject was included. SD-OCT was used to obtain 2D RNFL thickness values and 5 neuroretinal rim parameters [ie, 3D minimum distance band (MDB) thickness, 3D Bruch's membrane opening-minimum rim width (BMO-MRW), 3D rim volume, 2D rim area, and 2D rim thickness]. Main outcome measures: Area under the receiver operating characteristic curve values, sensitivity, and specificity. Results: Comparing all 3D with all 2D parameters, 3D rim parameters (MDB, BMO-MRW, rim volume) generally had higher area under the receiver operating characteristic curve values (range, 0.770 to 0.946) compared with 2D parameters (RNFL thickness, rim area, rim thickness; range, 0.678 to 0.911). For global region analyses, all 3D rim parameters (BMO-MRW, rim volume, MDB) were equal to or better than 2D parameters (RNFL thickness, rim area, rim thickness; P -values from 0.023 to 1.0). Among the three 3D rim parameters (MDB, BMO-MRW, and rim volume), there were no significant differences in diagnostic capability (false discovery rate >0.05 at 95% specificity). Conclusions: 3D neuroretinal rim parameters (MDB, BMO-MRW, and rim volume) demonstrated better diagnostic capability for primary and secondary open-angle glaucomas compared with 2D neuroretinal parameters (rim area, rim thickness). Compared with 2D RNFL thickness, 3D neuroretinal rim parameters have the same or better diagnostic capability.